A study on needle stick injuries among health care workers in a tertiary care hospital in India - Bashir, Humaira; Qadri, Syed Shuja (International Journal of Research in Medical Sciences, 2019)
Background: Needle stick injury among health workers is regarded as an occupational hazard. Health care workers are at risk of having blood-borne diseases in case they are exposed to blood and other biological samples of the patients. Moreover, staff including doctors working in tertiary care hospitals has high work load which results in increased chances of getting these injuries. The aim and objectives of this study were to find out the prevalence of needle stick injury among different categories of health care workers. Authors also aimed to assess the knowledge, attitude and practices associated with it. Methods: A hospital based cross sectional study design to know the prevalence of needle stick injury among various health care workers of Karpagam Faculty of Medical Sciences and Research, a tertiary level care hospital in Coimbatore, Tamilnadu, India. A total of 250 health care workers were selected for the study purpose. A self-designed, semi-structured, pre-tested questionnaire was used to assess the prevalence of needle stick injuries and the factors associated with it. Results: A majority of health care workers (94%) knew about needle stick injury and 92% were aware that HIV can be transmitted through needle stick injury, 78.4% and 69.65% were aware of Hepatitis-B and Hepatitis-C transmission respectively. About 28.4% of subjects had encountered needle stick injury in their past. Furthermore, it was found that type of exposure and place of exposure was significantly associated with different categories of health care workers (p <0.001). Conclusions: Prevention of health workers against needle stick injury is the best possible way to prevent several bloods borne diseases. There should be a prevention programme which special focus on training of health care workers. Further strategies aiming at preventive measures and reporting of the Needle stick injuries accidents should be made compulsory among health care workers.